What are metal prices like? Co-movement, price cycles and long-run trends - Anja Rossen (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2014)
This study explores the dynamics of monthly metal prices during the past 100 years. On the basis of a unique data set, co-movement, price cycles and long-run trends are analyzed by means of common statistical methods and the results are compared to the findings in the literature. Due to its large number of monthly observations (1224) and high number of price series (20), this data set has a huge advantage. Findings suggest that some results in the literature are specific for non-ferrous and precious metals and do not necessarily carry over to other metals like steel alloys, electrical metals, light metals, steel or iron ore. However, other results in the literature can be confirmed by the analysis of this comprehensive data set.
Keywords: C41; E32; Q31; 330; metal prices; co-movement; price cycles; super cycles